A BIBLIOMETRIC-ASSISTED LITERATURE REVIEW AND PROPOSED CONCEPTUAL FRAMEWORK OF CONSUMER BEV ADOPTION - Muhammad Ridzky Hanura; Wahyudi Sutopo; Yuniaristanto (RADJA PUBLIKA, 2026)
This study reviews and synthesizes the literature on consumer adoption of battery electric vehicles (BEVs) to construct a proposed comprehensive conceptual framework. Although previous research has identified multiple determinants of BEV adoption, findings remain fragmented across psychological, economic, technological, policy, and social domains, limiting a comprehensive understanding. To address this gap, this study employs a bibliometric-assisted systematic literature review, following PRISMA-2020 and SPAR-4-SLR guidelines, covering Scopus-indexed publications from 2015 to 2025. A total of 198 studies were analyzed. The findings show that most studies on BEV still focus on adoption intentions and factor-based approaches, while studies on actual adoption behavior and post-adoption phases remain limited. Bibliometric mapping identifies strong thematic clusters, but the relationships between domains are still weak, indicating the need for a more process-oriented explanatory approach. Therefore, this study developed a proposed conceptual framework that conceptualizes BEV adoption as a gradual decision-making process. The framework integrates perceived technological attributes, value and risk evaluations, attitudes, intentions, and actual adoption, with policy and social contexts acting as moderating factors. Overall, this research contributes by shifting the focus from intention-based perspectives to a cross-domain, process-oriented understanding, offering a foundation for future empirical studies and policy development